Profissionais da educação tecnológica: desafios da formação politécnica - Eckstein, Luiz Carlos (2018)
This thesis aims to examine the training of technology education professionals, from the understanding of polytechnics, with the quality is necessary to meet the dictates of contemporary. This is a historical-critical research that works on the theoretical conceptions, pertinent to the theme, respecting what is the basis of this work: historical materialism. In particular, Marx and Gramsci are envolved, especially with regard to polytechnics and the training of professionals in education. Still, it contemplates questions that hinder a work of quality formation in the institution of public education, attempting to understandthe training of the education professional in the determinations of today's world and identifying the problems that make it impossible for the development of quality educational work in the institution of technological education. As a methodological resource, the dialectical conception supports the case study. It was aimed to investigate, in the empirical pole, a Public Education Institution, of mediumsize, of Paraná State. Interviews were carried out, using specific instruments, with the teachers, to verify the existence of a training policy for their education professionals, as well as those who consider this training important. It was also sought to know the understanding that these professionals have about polyethnic as a challenge, for the quality of the professional exercise in the world of work. In the midst of the analysis of the data, in the light of the theoretical-methodological foundations, the almost total lack of knowledge of what has become polytechnics was contacted by the professionals who answered the investigation, similarly to the evidence that their training is restricted to the technical contents of their degree. It was also verified the need to understand that the construction of a training policy conceived in the polytechnic for the professionals of the technological education will bring significant contributions to the work of these professionals and, consequently, for the students and for those who will be committed to the formation aimed at true human citizenship and the world of the work of its academics.